Risk factors and outcomes in patients who switched from peritoneal dialysis to physician-oriented or patient-oriented kidney replacement therapy - Liu Zhang; Xu Guan; Liang Liu; Yinghui Huang; Jiachuan Xiong; Jinghong Zhao (Renal Failure)
Background We aimed to compare the cardiovascular events and mortality in patients who underwent either physician-oriented or patient-oriented kidney replacement therapy (KRT) conversion due to discontinuation of peritoneal dialysis (PD).Methods Patients with end-stage kidney disease who were receiving PD and required a switch to an alternative KRT were included. They were divided into physician-oriented group or patient-oriented group based on the decision-making process. Logistic regression analysis was used to explore the influencing factors related to KRT conversion in PD patients. The association of physician-oriented or patient-oriented KRT conversion with outcomes after the conversion was assessed by using Cox proportional hazards models.Results A total of 257 PD patients were included in the study. The median age at catheterization was 35 years. 69.6% of the participants were male. The median duration of PD was 20 months. 162 participants had patient-oriented KRT conversion, while 95 had physician-oriented KRT conversion. Younger patients, those with higher education levels, higher income, and no diabetes were more likely to have patient-oriented KRT conversion. Over a median follow-up of 39 months, 40 patients experienced cardiovascular events and 16 patients died. Physician-oriented KRT conversion increased nearly 3.8-fold and 4.0-fold risk of cardiovascular events and death, respectively. After adjusting for confounders, physician-oriented KRT conversion remained about a 3-fold risk of cardiovascular events.Conclusion Compared to patient-oriented KRT conversion, PD patients who underwent physician-oriented conversion had higher risks of cardiovascular events and all-cause mortality. Factors included age at catheterization, education level, annual household income, and history of diabetes mellitus.